What is the answer to double 7 multiply 3 and 1 and then subtract the second from the first number

Answers

Answer 1
Answer: Double 7= 7+7 which is 14, 3 times 1 = 3, and 2nd num is 3, so 3 minus 14 is 11, Hope i helped!!

Related Questions

There are 100 pennies in a dollar. What fraction of a dollar is 61 pennies? Write it as a fraction, as a decimal,and in word form
Sarah is 9 years old her grandfather is 90 how many times old as Sarah
A (-16) + (-16) =b (-16) - (-16) = c (+16) + (-16) = d (+16) - (-16) = e (+16) + (+16) = f (+16) - (+16) = g (-16) + (+16) = h (-16) - (+16) = AYUDAA
One reading at an arctic research station showed that the temperature was -35c. what is this temperature in degrees fahrenheit?please answer, and show work.
Patrick ate 3/5 of a small pizza. For lunch Saturday he4 ate 1/2 of the leftover pizza. How much pizza did he eat for lunch on Saturday?

3a + 2 - 5a = -14. Can someone solve this for me.

Answers

Answer:

a=8

Step-by-step explanation:

3a + 2 - 5a = -14

Combine like terms

-2a +2 = -14

Subtract 2 from each side

-2a +2-2 = -14-2

-2a = -16

Divide each side by -2

-2a/-2 = -16/-2

a = 8

Answer:

a = 8

Step-by-step explanation:

-2a + 2 = -14

-2a = -16

-16/-2 = 8

a = 8

Which expression is equivalent to this expression


t - 6(-2t + 1)

Answers

The correct expression which is equivalent to this expression t - 6(-2t + 1) is,

⇒ 13t - 6

What is an expression?

Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.

We have to given that;

The expression is,

⇒ t - 6 (- 2t + 1)

Now, We can simplify as;

⇒ t - 6 (- 2t + 1)

⇒ t + 12t - 6

⇒ 13t - 6

Thus, The correct expression which is equivalent to this expression

t - 6(-2t + 1) is,

⇒ 13t - 6

Learn more about the mathematical expression visit:

brainly.com/question/1859113

#SPJ3

t - 6( - 2t + 1) \n t  + 12t - 6 \n 13t - 6 \n 13t = 6 \n t =  (13)/(6)

What number should be added to the expression to turn it into a perfect square trinomial x^2+2x

Answers

kinda like completing the square
if you have
ax^2+bx+c
a=1 for ease

take b and halve it then square that
then make c= that

x^2+2x+c
a=1 good
b=2
2/2=1
1^2=1
x^2+2x+1
(x+1)^2

the number 1 should be added

Solutions 

A Perfect Square Trinomial is the product of two binomials. Both the binomials are same. When you multiply an algebraic expression with two terms to itself, you will get a three-term expression called a perfect square trinomial. A perfect square trinomial is one that factors into two identical factors. The general forms of perfect square trinomial are = 

(ax - b)² = (ax)² - 2axb + b² and (ax + b)²= (ax)² + 2axb + b²

Calculations 

αx²+βx+c

The variable α = 1 for ease

Take the variable b and half it then square that
to make c = number

x²+2x+c

variable α = 1 

variable β = 2 

2 ÷ 2=1

1² = 1 

x²+2x+1

(x+1)² 

In conclusion the number (1) should be added to the expression to turn it into a perfect square trinomial . 

In a arithmetic sequence with a^1=12, d=3 which term is equal to 159?

Answers

Answer:

50th term is 159

Step-by-step explanation:

nth term=159

a + (n -1)*d = 159

12 + (n-1)*3= 159

(n - 1)*3 = 159 - 12

(n - 1)*3 = 147

n -1 = 147/3

n - 1 = 49

n = 49 + 1

n= 50

Answer: n=50th term

Step-by-step explanation:

An= a1+(n-1)d

An= nth term

A1= first term

N= nth position

D= common difference

An =159

A1= 12

D= 3

N= ?

Substitute the values

An=a1+(n-1)d

159=12+(n-1)3

Collect like terms

159-12=(n-1)3

147=3n-3

147+3=3n

150=3n

N=150/3

N= 50

Therefore 50th term will give 156

Rewrite the equation 5x-8y+3=5x-7t+2 into general form (ax+by+c=0). A. x-1=0
B. x+1=0
C. y-1=0
D. y-3=0

Answers

I'm answering this assuming that you accidentally wrote 7t instead of 7y.

5x - 8y + 3 = 5x - 7y + 2  

- (5x - 8y + 3)    -(5x - 8y +3)

0 = y - 1 or y-1 = 0

The answer is C.

Hope I helped!




Translate the sentence into an inequality.
The product of b and 6 is less than - 16.

Answers

Answer:

6b<-16

Step-by-step explanation:

Final answer:

The sentence 'The product of b and 6 is less than -16' translates to the inequality '6b < -16' in Mathematics.

Explanation:

In mathematics, translating a sentence into an inequality involves identifying the mathematical symbols and operations represented by the words in the sentence. In this case, 'the product of b and 6' translates to '6 * b' and 'is less than' translates to '<'. So, the sentence 'The product of b and 6 is less than -16' translates to the inequality '6 * b < -16' or '6b < -16' in simplified form.

Learn more about Inequalities here:

brainly.com/question/32625151

#SPJ3